IMG Doctors’ Experience of Starting Their First Job in the UK – Cross-Sectional Survey Study - Marium Imran; Mahmoud Abdelaal; Raja Adnan Ahmed (BJPsych Open, 2025)
Aims: To identify the difficulties International Medical Graduate (IMG) doctors face when starting their first job in the UK.